DEVELOPMENT PERSPECTIVES FOR FOREIGN MNC’s ON THE RUSSIAN ENERGY MARKET - Evgeny V. Ryabinin (Статистика и экономика, 2016)
The methodological and methodical basesof research of foreign MNC’s on Russian fuel and energy market are stated in thearticle. The great attention is focusedon analysis of dependence of the Russian economy from foreign MNCs. Thecomparison of competitiveness to activityof foreign MNC’s in other sectors of the Russian economy. It is marked basicproblems and barriers of foreign TNCsactivities in the Russian fuel and energymarket, as well as the main advantagesand disadvantages for Russia as for thehost country.